The Intraday Behaviour of Bid-Ask Spreads Across Auction and Specialist Market Structures: Evidence From The Italian Market - D. Gerace; A. Lepone (Australasian Accounting, Business and Finance Journal, 2010)
Several studies have analysed liquidity across a trading day, and have documented that bid-ask spreads exhibit a U-shaped pattern, with spreads wider at the start and end of the trading day, whilst spreads are tighter in the middle of the day. This pattern has been attributed to inventory holding costs, the specialist’s market power and adverse selection risk. On the 2nd April, 2001, several stocks on the Italian Bourse switched from an auction market to a specialist market. This provides a natural experiment where intraday spreads across different market structures can be compared. Results indicate that volume, volatility and bid-ask spreads exhibit the U-shaped intraday pattern both before and after the structural change. While time-weighted spreads are consistently higher throughout the trading day under the specialist structure, the specialists ability to offer price improvement with the best quotes results in the ‘real’ cost of trading being lower under a specialist system. These results are robust to the size of the firm, the event window around the structural change, as well as overall market-wide changes.
Keywords: era2015